2021
DOI: 10.3390/fermentation7040267
|View full text |Cite
|
Sign up to set email alerts
|

Value-Added Products from Ethanol Fermentation—A Review

Abstract: Global demand for renewable and sustainable energy is increasing, and one of the most common biofuels is ethanol. Most ethanol is produced by Saccharomyces cerevisiae (yeast) fermentation of either crops rich in sucrose (e.g., sugar cane and sugar beet) or starch-rich crops (e.g., corn and starchy grains). Ethanol produced from these sources is termed a first-generation biofuel. Yeast fermentation can yield a range of additional valuable co-products that accumulate during primary fermentation (e.g., protein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 143 publications
0
7
0
Order By: Relevance
“…VOCs can be formed in meat in the course of Maillard reaction, alcoholic fermentation, , microbial activity, and lipid oxidation . The presence of acetic acid, ethyl acetate, and butanol is attributed to microbial activity during ham spoilage .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…VOCs can be formed in meat in the course of Maillard reaction, alcoholic fermentation, , microbial activity, and lipid oxidation . The presence of acetic acid, ethyl acetate, and butanol is attributed to microbial activity during ham spoilage .…”
Section: Resultsmentioning
confidence: 99%
“…We observed that the intensities of ethanol and acetone were higher in the spoiled ham than in the fresh and semispoiled ham (Figure ). The ethanol production in ham can be associated with alcoholic fermentation, indicating the occurrence of microorganisms such as yeast or bacteria, which enzymatically convert sugars present in ham into ethanol. , On the other hand, acetone may indicate the occurrence of early-stage degradation of muscle glycogen . The following VOCs were also found in the semispoiled and spoiled ham samples: ethylene ( m / z 29.0386), acetic acid ( m / z 61.0284), butanol ( m / z 75.0804), and eugenol ( m / z 165.0910).…”
Section: Resultsmentioning
confidence: 99%
“…Fermentation using yeast (typically Saccharomyces cerevisiae) converts the sugar to ethanol, with many factors affecting the final ethanol yield [113]. After fermentation, the mixture, called beer, is transferred to a distillation system where ethanol is distilled from the beer [13]. Finally, the ethanol mixture is further purified through rectification and dehydration, resulting in a final ethanol concentration of 95% or higher [114].…”
Section: Wheat Grain In Biofuel Productionmentioning
confidence: 99%
“…During fermentation of wheat grain, additional value-added compounds are also produced including glycerol, succinic acid, acetic acid, lactic acid, and α-glycerylphosphorylcholine (e.g., a nootropic compound) [13,118]. The nootropic compound α-GPC has been investigated as a treatment for Alzheimer's disease and strokes [119].…”
Section: Wheat Grain In Biofuel Productionmentioning
confidence: 99%
See 1 more Smart Citation